2023
DOI: 10.15741/revbio.10.e1404
|View full text |Cite
|
Sign up to set email alerts
|

EN PRENSA. Efecto insecticida del extracto metanólico de Argemone mexicana para el control de Bactericera cockerelli (Sulc.) (Hemiptera: Triozidae).EN PRENSA

Abstract: Argemone mexicana L. es una maleza, la cual es utilizada como planta medicinal. La actividad biológica de esta planta se ha observado en patógenos como virus, hongos, bacterias, protozoos y plagas de cultivos agrícolas; dicha actividad se atribuye a compuestos como flavonoides, glucósidos, terpenoides, compuestos fenólicos y alcaloides presentes en la planta. El objetivo del estudio fue evaluar el efecto del extracto metanólico de A. mexicana como insecticida sobre Bactericera cockerelli. Se detectaron 13 meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…Aqueous extracts of Posidonia oceanica revealed that phenolic compounds, glycosides, and terpenes played a crucial role in the development of the roots and leaves of S. lycopersicum and Cucumis sativus [22]. The methanolic extracts of C. longirostrata and A. mexicana used in this study contain secondary metabolites previously identified as significant components in these plants [23,24].…”
Section: Introductionmentioning
confidence: 62%
See 2 more Smart Citations
“…Aqueous extracts of Posidonia oceanica revealed that phenolic compounds, glycosides, and terpenes played a crucial role in the development of the roots and leaves of S. lycopersicum and Cucumis sativus [22]. The methanolic extracts of C. longirostrata and A. mexicana used in this study contain secondary metabolites previously identified as significant components in these plants [23,24].…”
Section: Introductionmentioning
confidence: 62%
“…In addition, the results of gas chromatography and mass spectrophotometry showed the presence of secondary metabolites in the extracts, which could be responsible for their capacity to stimulate plant growth. The methanolic extracts of A. mexicana and C. longirostrata presented a 72.6% and 79.9% abundance of these compounds, respectively; these metabolites belong to the groups of saturated and unsaturated fatty acids, amines, fatty alcohols, alkaloids, and cyanogenic glycosides [23,24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation